PENEGAKAN HUKUM PEREDARAN MINUMAN MENGANDUNG ETIL ALKOHOL ILEGAL TANPA CUKAI BERDASARKAN UNDANG-UNDANG NOMOR 39 TAHUN 2007 PERUBAHAN ATAS UNDANG-UNDANG NOMOR 11 TAHUN 1995 TENTANG CUKAI DI WILAYAH HUKUM KANTOR PENGAWASAN DAN PELAYANAN BEA DAN CUKAI (KPPBC) TIPE MADYA PABEAN B KOTA TANJUNGPINANG - Tri Handika Putra; Erdianto Effendi; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Excise also known as state’s charge imposed for some specific commodities which have characteristics written in law, it functions as state’s income for the need of public welfare. The distribution of illegal Alcohol without excise in Tanjungpinang uses some operating mode such as the distribution of plain Alcohol without excise and the distribution of Alcohol in the free trade zone, until now none of the cases related to the distribution of illegal Alcohol processed in the trial. Hence, there are a lot of questions related to the cases and the public are wondering why the distributions seems so legal among the society even though there are some distributors that have been arrested. The objectives of this research are; first, the law enforcem ent of the distribution of illegal Alcohol without excise. Second, the obstacles found during the law enforcement of the distribution of illegal Alcohol without excise. Third, the efforts made to overcome the obstacles in law enforcement of the distribution of illegal Alcohol without excise.The conclusion of this research are; First, the Directorate General of Customs and Excise did some preventive actions such as conducting a law counselling, observation and patrolling, whereas in the repressive way they arrest the litigants, confiscating or prohibiting the distribution of illegal commodities and market operation. Second, the obstacles found during the law enforcement are internal factors such as lack of staffs and operational facilities. While, the external factors are the boundaries of free trade zone are not clear, role of society and small traders which is less and the difficulty in finding the illegal distributors of Alcohol. Third, the efforts made to fix the problems related to customs and excise are by proposing the addition of staffs in the Directorate General of Customs and Excise and adding the operational facilities. In addition, other external parts that have to be considerate are by improving the security of Sri Bintan Pura Tanjungpinang as an international harbour, patrolling and coordinating with The Indonesian Navy, raising the awareness, law-abiding and doing some observation with the intelligence team.The writer’s suggestions related to the problems of this research are; first, the writer hopes the solutions may reach the small traders and the distributors of illegal Alcohol without excise. Second, for the government as the policy maker may find some ways to make the boundaries of free trade zone become clearer. Third, the government can enforce the criminal sanctions of excise.Key Words: Law Enforcement – Distribution – Alcohol without Excise